2009
DOI: 10.2147/clep.s4759
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic characteristics and risk factors for renal cell cancer

Abstract: Abstract:Incidence rates of renal cell cancer, which accounts for 85% of kidney cancers, have been rising in the United States and in most European countries for several decades. Family history is associated with a two-to four-fold increase in risk, but the major forms of inherited predisposition together account for less than 4% of renal cell cancers. Cigarette smoking, obesity, and hypertension are the most consistently established risk factors. Analgesics have not been convincingly linked with renal cell ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 176 publications
(182 reference statements)
0
13
0
3
Order By: Relevance
“…However, credible or consistent associations of these factors with renal cell cancer have not been reported, and they do not play an obvious role in explaining the unusual patterns of renal cell cancer incidence and mortality among blacks and whites. The collective epidemiologic evidence related to these characteristics and risk factors has been addressed by the authors in detail elsewhere [ 102 , 103 ] and, therefore, will be mentioned here only in brief.…”
Section: Resultsmentioning
confidence: 99%
“…However, credible or consistent associations of these factors with renal cell cancer have not been reported, and they do not play an obvious role in explaining the unusual patterns of renal cell cancer incidence and mortality among blacks and whites. The collective epidemiologic evidence related to these characteristics and risk factors has been addressed by the authors in detail elsewhere [ 102 , 103 ] and, therefore, will be mentioned here only in brief.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the most cases controlled studies have demonstrated a dose-response relationship (14). The risk of developing renal cell cancer is increased for lifelong smokers who smoke more than 20 cigarettes per day (relative risk 2.1) compared with those who smoke <10 cigarettes per day (relative risk 1.1), and the risk appears to be high for smokers who started at an earlier age (15).…”
Section: Overuse Of Cigarettes Smoking and Kidney Cancermentioning
confidence: 99%
“…The risk of developing renal cell cancer is increased for lifelong smokers who smoke more than 20 cigarettes per day (relative risk 2.1) compared with those who smoke <10 cigarettes per day (relative risk 1.1), and the risk appears to be high for smokers who started at an earlier age (15). Conversely, the risk seems to decline significantly by the number of years after cessation, leading to a 25-30% reduction in risk after 10-15 years of cessation (14).…”
Section: Overuse Of Cigarettes Smoking and Kidney Cancermentioning
confidence: 99%
“…Renal cell cancer represents about 85% of kidney cancers, and renal pelvis cancer comprising the rest of kidney cancer cases ( Lipworth et al , 2009 ). The mean age at diagnosis for renal cell cancer is in the early 60s, and in the late 60s for renal pelvis cancer ( Lipworth et al , 2009 ). The 5-year survival rate for localized renal cell cancer cases is about 90% ( Lipworth et al , 2009 ).…”
Section: Introductionmentioning
confidence: 99%